Pelatihan Merancang Sistem Informasi Akuntansi Accurate Pada PT. Mahatani Kota Bogor - Harry Roestiono; Suharmiati Suharmiati (Jurnal Abdimas Dedikasi Kesatuan, 2021)
MSMEs (Micro, Small and Medium Enterprises) in Indonesia are one of the most dominant business sectors run by business actors. Processing of data related to financial statements is carried out using an excel data manual system in Microsoft office, this causes obstacles in calculating financial transactions, both in the form of cash turnover on sales and at the same time merchandise inventory turnover, also experiencing delays in making financial reports. Management of financial data and inventory in the preparation of financial statements, requires accuracy and accuracy of data data in every decision making. In accordance with current technological developments, it is hoped that MSMEs that already have a turnover of the upper middle class will already use a computer accounting information system. To assist in preparing financial reports using an accurate accounting information system, through this training, it is hoped that data results are updated, accurate, and quickly provide information to management. Training on Designing Accurate Accounting Information Systems at PT. Mahatani in Bogor City, can provide an overview of how it works and design concepts that are easily understood by system users/users to help make it easier to prepare financial reports. The required transactions have been provided for accurate activities, starting from creating a new account with the name of the company, along with the chart of account number, updating the chart of account according to the needs of the account number designed by management to facilitate account classification. The accurate accounting information system can be done with multi users, so that all departments can input transaction data together with the aim of providing financial information for management. The ultimate goal of accounting records is to produce a good and accurate report that is expected to provide an actual picture of the company's financial activities. Accurate, which is an integrated program, provides financial reporting facilities that make it very easy for users. Especially the Accurate database system which allows every financial activity that occurs and is recorded in the system to be extracted when it is summarized into a report Keywords: Designing Accurate Accounting Information System at PT. Mahatani.